HUBUNGAN PENGALAMAN BERORGANISASI DENGAN TINGKAT ADVERSITY QUOTIENT (AQ) PADA MAHASISWA ANGKATAN 2012 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Diva Yurian Dwika; Zulharman "; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAdvance level of Adversity Quotient (AQ) is essential for medical students to gain struggling power in facing the challenges along the study to become a good and successful doctor. Many factors affect people Adversity Quotient (AQ) level, one of them is organization. The level of Adversity Quotient (AQ) depends on life experiences, without exception; organizational experience. The objective of this research was to find out the correlation of organizational experience and Adversity Quotient (AQ) level in medical students year 2012 of university of Riau. This research is an analytical research with cross sectional approach. The subject of the research are medical students year 2012 of university of Riau. Sample of the research consists of 115 medical student which is collected by total sampling technique. The researcher uses a questioner based on organization theories and researches, then adopted Stoltz's theories on Sari's research. The statistic assessment of correlation between organizational experience and Adversity Quotient (AQ) level; uses Spearman's Correlation test. Result of the research shows that there is a significant correlation between organizational experience and Adversity Quotient (AQ) level (r=0,345; p=0,000). The Finding of the research shows that there is a correlation between organizational experience and Adversity Quotient (AQ) level in medical students year 2012 of university of Riau.keyword : organization experience, adversity quotient, medical students